2013
DOI: 10.1016/j.jbiotec.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Viral protein-coating of magnetic nanoparticles using simian virus 40 VP1

Abstract: Artificial beads including magnetite and fluorescence particles are useful to visualize pathologic tissue, such as cancers, from harmless types by magnetic resonance imaging (MRI) or fluorescence imaging. Desirable properties of diagnostic materials include high dispersion in body fluids, and the ability to target specific tissues. Here we report on the development of novel magnetic nanoparticles (MNPs) intended for use as diagnosis and therapy that are coated with viral capsid protein VP1-pentamers of simian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…In this study, we have examined the feasibility of assembling proteinaceous AaLS‐13 shells around inorganic nanomaterials . Spherical gold nanoparticles (AuNPs) are useful for drug delivery, for photocatalysis, as biological sensors, and as conjugation platforms for oligonucleotides and biomolecules .…”
Section: Figurementioning
confidence: 99%
“…In this study, we have examined the feasibility of assembling proteinaceous AaLS‐13 shells around inorganic nanomaterials . Spherical gold nanoparticles (AuNPs) are useful for drug delivery, for photocatalysis, as biological sensors, and as conjugation platforms for oligonucleotides and biomolecules .…”
Section: Figurementioning
confidence: 99%
“…There are a considerable number of studies taking advantage of such structural features to equip functional motifs on SV40 VNPs. For example, enhanced green fluorescence protein (EGFP) was fused to the N‐terminus of VP1 to visualize the behavior of SV40 VNPs in living cell; therapeutic Hirulog peptide was fused to the N‐terminus while targeting peptide was inserted into the HI loop or the DE loop of VP1 for targeted treatment of atherosclerotic plaques; human epidermal growth factor (hEGF) was chemically conjugated to the DE loop via the hetero‐bifunctional crosslinker SM(PEG) 2 for targeting cells overexpressing the EGF receptor . Also, the internal proteins VP2 and VP3 can be used to fuse cargo peptides and proteins.…”
Section: Vnps Derived From Sv40mentioning
confidence: 99%
“…SV40 VNPs have exhibited good compatibility in encapsulating nanomaterials with different components, shapes, sizes and surface properties. A series of nanoparticles (NPs) including CdSe@ZnS quantum dots (QDs), Ag 2 S QDs, gold NPs (AuNPs), citrate‐coated magnetic NPs (MNPs) have been encapsulated by SV40 VNPs through self‐assembly, with one NP core inside one VNP (Figure ). An effort to explore the NP‐induced SV40 VNP assembly mechanism found that there was a strong affinity between QDs and SV40 VP1 pentamers (K D = 2.19E‐10 M), which should play an important role in driving QD encapsulation in SV40 VNPs .…”
Section: Sv40 Vnps For Nanobiotechnological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, varying the ratio of linear DNA to capsid subunit of SV40 can be used to control size, shape, and stability of virus-like particles (Mukherjee et al, 2010). unrivaled flexibility in the lateral interactions between polyomavirus capsid subunits allows them to assemble on cores considerably larger or smaller than the native 50 nm capsid, while maintaining a regular subunit lattice, for example polystyrene beads of 100 and 200 nm (Figure 1B; (Kawano et al, 2015)), or the much smaller 8, 20, and 27 nm citrate-coated oleate-iron nanoparticles (Enomoto et al, 2013). …”
Section: Viruses and Virus-like Particlesmentioning
confidence: 99%